THE EFFECT OF PROCESS ORIENTED GUIDED INQUIRY LEARNING (POGIL) MODEL ON STUDENTS' CONCEPTS MASTERY - Pradiyanasari, Ni Wayan Erisca; Verawati, Ni Nyoman Sri Putu; Doyan, Aris (Lensa: Jurnal Kependidikan Fisika, 2020)
This study aims to determine the effect of the Process Oriented Guided Inquiry Learning (POGIL) model on the students? concept mastery in SMAN 6 Mataram, subject matter of harmonious vibration. This study is a quasi-experimental research with a pretest-posttest control group design. The population was all students of class X MIA at SMAN 6 Mataram in the 2018/2019 academic year totaling 172 students, with purposive sampling technique obtained by class X MIA 1 as an experimental class and class X MIA 3 as a control class. The concept mastery test instrument uses multiple choice questions totaling 25 items. The concept mastery data obtained were analyzed using t-test with a significance level (?) of 5%. Hypothesis test results indicate that the t-count is greater than t-table, that is 2.482 is greater than 2.020, so that H0 is rejected and Ha is accepted. Thus, there is an effect of the Process Oriented Guided Inquiry Learning (POGIL) model on students' concept mastery.